Assessing native and non-native conformational states of a protein by methylene carbene labeling: the case of Bacillus licheniformis beta-lactamase - Ureta, Daniela Beatriz (2007)
Much knowledge of protein folding can be derived from the examination of the nature and size of solvent-exposed surfaces along conformational transitions. We exploit here a general photochemical modification with methylene carbene of the accessible surface area (ASA) of the polypeptide chain. Labeling of Bacillus licheniformis beta-lactamase (BL-betaL) with 1 mM 3H-diazirine yielded 8.3 x 10(-3) mol CH2/mol protein, in agreement with the prediction for an unspecific surface labeling phenomenon. The unfolded state U in 7 M urea was labeled 60% more than the native state N. This result lies well below the increment of ASA expected from theoretical estimates and points to the presence of residual organization in state U and/or of cavities or crevices favoring the partition of the reagent in state N. A partially folded state I was demonstrated from two sequential transitions occurring at 1.5-3.0 M and 3.5-6.5 M urea. This technique shows a close correlation with optical probes most sensitive to changes in tertiary structure, a statement supported by the fact that the largest change occurs along the N-I portion of the N-I-U transition and along the acid pH-induced N-A transition. In the latter case, state A is labeled 70% more than state N, an increment consistent with the loosening of tight interactions in the core of the protein. Fragmentation of labeled BL-betaL into peptides provides a sequential map of solvent accessibility. Thus, amino acid residues pertaining to the Omega-loop and to helices alpha5 and alpha6 line the major cavity of the protein, that is big enough to lodge the diazirine reagent. Methylene labeling, by introducing an original (and perhaps unique) experimental measurement of ASA, enlightens subtle aspects of complex transitions and makes possible a comparative structural characterization of the native as well as non-native states